HOLISTIC PARENTING COMMUNICATION STRATEGIES FOR CULTIVATING SUPUTRA VALUES IN CHILDREN’S CHARACTER - Suhardi, Untung; Komang Agung Sukra Adnyana (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2025)
Family life is the main concern to mold the next generation and the future of the family. The existence of the family is sometimes hampered due to parenting and communication that is not done properly in the family. The subject of this problem discusses the parenting style of children in family life and communication strategies to form children who are suputra. The method used in this study is qualitative analysis with a phenomenological approach and a relational dialectic analysis knife. The findings of this study are the types of (a) authoritarian parenting, (b) democratic parenting, (c) permissive parenting, (d) situational parenting.  The parenting style applied by parents has a profound impact on the formation of their children's character. The approach to relational dialectics emphasizes the importance of open and constructive dialogue between parents and children. Parents are not only the authority that gives orders, but also partners in the learning process and growth of their children. Parents can help children develop problem-solving and decision-making skills that are essential for facing life's challenges. The education provided by parents to children should be oriented to the needs of children as biopsychosocial-religious beings and use methods that are in accordance with the development of children, both their physical-biological development, their psychological development, social development and the development of their religiosity. Communication strategies that can be built are Setting a Positive Example, Talking About Moral Values, Giving Praise and Reward, Gently Giving Direction and Correction, Talking About the Consequences of Actions, Setting Clear Rules and Boundaries, and Making Time for Family Quality.